ANALISIS KUALITAS AIR DANAU SEBAGAI DASAR PERBAIKAN MANAJEMEN BUDIDAYA PERIKANAN DI DANAU BUYAN KABUPATEN BULELENG, PROVINSI BALI - Riki Saputra, I Wayan Rian; Restu, I Wayan; Ayu Pratiwi, Made (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 11 No 1 (2017), 2017)
LAKE WATER QUALITY ANALYSIS AS A IMPROVEMENT BASIS OF AQUACULTURE MANAGEMENT IN BUYAN LAKE REGENCY OF BULELENG, BALI PROVINCE Buyan Lake is one of the lakes in Bali province. That located at Pancasari Village, District of Sukasada, Buleleng Regency. This lake they are many utilication of the lake such as agriculture, tourism and aquaculture activities. Those activities are considered to contribute an eutrophication in this lake. In order to investigate the effect of of floating net cages activity in Buyan Lake, the research about “The Analysis of Water Quality as a Basic Improvement of Aquaculture Management in Buyan Lake” was conducted This research method used in this study was done by observation method and took the samples in situ (at Buyan Lake site) and samples analysis was done by ex situ (at UPT. Laboratorium Kesehatan Propinsi Bali). They were 2 water quality parameters such as some physic parameters (temperature, clarity and turbidity) and chemistry parameters (pH, DO, ammonia, nitrate, BOD, COD, sulfide and phosphate). The data analysis of this research was analysis conducted by STORET index and pollution index (PI). Base on the analysis using STORET index, pollution status in Buyan Lake was heavily contaminated with average score of -82. The highest score was obtained in station 3 (-98). The results of pollution index showed that Buyan Lake has a lightly contamination with average score 3,4347 whereas the highest pollution index score was obtained in sation 4 (3.8673).